Poverty Reduction and Growth Trust-Review of Interest Rate Structure. (Policy Papers; Policy Paper, 2019)
This paper reviews the Poverty Reduction and Growth Trust (PRGT) interest rate structure for the period July 2019-June 2021. Since the interest rate mechanism was first established in 2009, no interest has been charged on PRGT credit. In line with the package of reforms proposed in the parallel Review of LIC Facilities, this paper proposes to align interest rates on the SCF with those on the ECF. Based on the average SDR rate over the most recently observed 12-month period, the proposed revised interest rate mechanism would result in zero interest rates on both ECF and SCF credit for the period July 2019-June 2021.